Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Hotel Jeep Station Indonesia Resort Megamendung Bogor - Muhammad Maulana Iqbal; Dewi Kurniawati (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Influence of Work Discipline and Work Motivation on Employee Performance at Hotel Jeep Station Indonesia Resort Megamendung Bogor This study aims to examine the effect of work discipline and work motivation on employee performance at Hotel JSI Resort Megamendung Bogor. The study is grounded in the importance of employee performance in supporting hotel service quality, particularly because service excellence is closely related to employees’ discipline, responsibility, and work encouragement. This research employed a quantitative method with an associative approach. The population and sample consisted of all 40 employees of Hotel JSI Resort Megamendung Bogor, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS 31. The findings indicate that work discipline has a positive and significant effect on employee performance. This suggests that higher levels of employee discipline contribute to better performance outcomes. In contrast, work motivation was not found to have a significant partial effect on employee performance. Therefore, it can be concluded that work discipline is an important factor in improving employee performance at Hotel JSI Resort Megamendung Bogor, whereas work motivation has not been proven to directly and significantly influence employee performance.